Effect of local antimicrobial agents on excisional palatal wound healing: a clinical and histomorphometric study in rats - Avital Kozlovsky (Blackwell Synergy, 2007)
Aim: To assess the effect of topically applied antimicrobial agents on palatal excisional wound in rats. Materials and Methods: Excisional wounds, 5mm in diameter, were made in the centre of the palate of 125 Wistar male rats. In four experimental groups, chlorhexidine digluconate (CHX) 0.12% solution, 1% CHX gel, phenolic compounds solution (Listerines), amine/stannous fluoride solution (Meridols) and saline solution as a control group were applied daily for 1 min. The wound area was measured photographically and the epithelialization rate was determined histologically at 3, 7, 14 and 21 days post-surgery. Results: The mean wound area and mean distance between the epithelial margins decreased significantly with time (po0.001) in experimental and control groups, with the greatest wound area reduction and rate of epithelialization on day 14. A significantly superior rate of wound epithelialization ( p50.03) was presented following use of 1% CHX gel and Listerines and a comparatively inferior one when the Meridols solution was applied. Conclusions: Each tested antimicrobial agent when applied on an excisional wound with epithelial and connective tissue deficiency did not have a negative effect on the rate of wound closure. The best results were achieved with 1%CHX gel and Listerine